2017
DOI: 10.18632/oncotarget.20595
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 affects apoptosis and expression of death receptor and endoplasmic reticulum molecules in chicken spleen

Abstract: Aflatoxin B1 (AFB1) is a natural product of the Aspergillus genus of molds, which grow on several foodstuffs stored in hot moist conditions, and is among the most potent hepatocarcinogens and immunosuppression presently known. The latter was related to the up-regulated apoptosis of immune organs. However, the effect of expression of death receptor and endoplasmic reticulum molecules in AFB1-induced apoptosis of chicken splenocytes was largely unknown. The objective of this study was to investigate this unknown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…Thus, the histological changes might not have been sufficient to cause significant reductions in the relative weights of the immune organs. In general, the suppression of lymphoid organ growth induced by AFB 1 is related to reduced numbers of lymphocytes [72,73,74]. It has been reported [73,75] that the reduction in the relative weight of the bursa induced by AFB 1 can be attributed to the decreased diameter of the lymphoid follicles and the reduced number of lymphocytes.…”
Section: Effects Of Aflatoxin B1 Produced By Aspergillus Flavus Anmentioning
confidence: 99%
“…Thus, the histological changes might not have been sufficient to cause significant reductions in the relative weights of the immune organs. In general, the suppression of lymphoid organ growth induced by AFB 1 is related to reduced numbers of lymphocytes [72,73,74]. It has been reported [73,75] that the reduction in the relative weight of the bursa induced by AFB 1 can be attributed to the decreased diameter of the lymphoid follicles and the reduced number of lymphocytes.…”
Section: Effects Of Aflatoxin B1 Produced By Aspergillus Flavus Anmentioning
confidence: 99%
“…Cell, tissue and organ development, differentiation, proliferation and homeostasis is regulated by a process named apoptosis. Excessive apoptosis of several mammal and poultry cells such as hepatocytes, bronchial epithelial cells, bone marrow cells and renal cells was caused by AFB1 11 . The main intermediate filament protein which is known as desmin interacts with other proteins forming a continuous cytoskeletal network.…”
Section: Introductionmentioning
confidence: 99%
“…Pathomorphological studies have shown significant reduction in the density of lymphoid cells through lymphocytic degeneration [40,41,42]. Pathological changes in the spleen are thought to result from increased oxidative stress, decreased glutathione (GSH) levels and increased apoptosis [17,43]. Studies suggest that effects on the spleen are dependent on the effective exposure and genetic susceptibility of the birds.…”
Section: Discussionmentioning
confidence: 99%
“…Studies suggest that effects on the spleen are dependent on the effective exposure and genetic susceptibility of the birds. For example, Zhu et al [43] reported significantly lower relative spleen weights in broiler chickens fed AFB 1 -contaminated diets (0.8 mg AFB 1 /kg feed), whereas Peng et al [44] reported a significant increase (82–134 µg AFB 1 /kg). Grozeva et al [42] found significantly lower relative spleen weights in AFB 1 -fed commercial strain turkey poults (0.2 and 0.4 mg AFB 1 /kg), whereas Quist et al [25] reported slightly lower (non-significant) spleen weight in AFB 1 -fed wild turkeys (100–400 µg AFB 1 /kg).…”
Section: Discussionmentioning
confidence: 99%